Debus Banten: In Between Myth, Belief, And Culture - Sihombing, Lambok Hermanto; K, Aditya; H, Barik; A, Kerin (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
Debus is one of the martial arts from the province of Banten, Indonesia.It is considered an art that is still controversial about its origin because this art shows the ability of people who are immune to sharp weapons, hydrochloric acid, and other dangerous materials that can be very harmful to human. It is still debatable that Debus is being associated with religion or belief for there is some ritual that is conducted during the practice. By using Cultural Identity as our main theory and encoding-decoding theory by Stuart Hall, the authors try to find out whether Debus Banten is still relevant in this current society and unpack the complexity of the diverse comments appearing on YouTube regarding the tradition. The data is taken from the comments from YouTube videos that use Debus Banten as the content. The result of this study suggests that topics appearing in the comments are not limited to the fight or the fighters. Interestingly, the topic is also about a debate that Debus Banten is a pure traditional martial arts or black magic.